Simplify:
(1.5x - 4y) (1.5x + 4y + 3) - 4.5x + 12y
(1.5x - 4y) (1.5x + 4y + 3) - 4.5x + 12y
= 1.5x(1.5x + 4y +3) - 4y(1.5x + 4y +3) - 4.5x +12y
= (1.5x X 1.5x) + (1.5x X 4y) + (1.5x X 3) - (4y X 1.5x) - (4y X 4y) - (4y x 3) - 4.5x +12y
= 2.25x2 + 6xy + 4.5x - 6xy - 16y2 - 12y - 4.5x + 12y
= 2.25x2 + ( 6 - 6)xy + (4.5 - 4.5)x - 16y2 + (12 - 12)y
= 2.25x2 + 0 + 0 - 16y2 + 0
= 2.25x2 - 16y2
Consider the special case of Identity (IV) with a = b, what do you get? Is it related to Identity (1)?
Consider, the special case of Identity (IV) with a = –c and b = –c. What do you get? Is it related to Identity (II)?